The Influence of Framing Effects on Public Opinion of Antibiotic use in Livestock - Garrett M Steede; Courtney Meyers; Nan Li; Erica Irlbeck; Sherice Gearhart (Journal of Applied Communications, 2020)
After years of debates and opposition from pharmaceutical companies, the Final rule of the Veterinary Feed Directive (VFD) went into effect in January 2017 requiring antibiotics used for both humans and animals for the purpose of growth promotion to be discontinued. This study sought to determine the effects framing content regarding antibiotic use in livestock and antibiotic resistance had on public opinion. Using a between-subjects experimental survey research design, 297 respondents indicated their perceptions of antibiotic use in livestock and the development of antibiotic resistant bacteria before being randomly assigned to one of three conditions. Each condition was a mock Twitter account framed differently based on findings from previous studies. After reading their assigned mock Twitter page, respondents indicated their trust of the information contained in the account, their information seeking behavior, demographics, and their support for antibiotic use in livestock. Using an ANCOVA, results indicated the frame influenced trust of information (F = 8.7, p < .05) and information seeking behavior (F = 4.48, p = .01) while support was not significant (F = 2.7, p = .07). Results suggest the blame frame has the greatest influence on shaping public opinion of antibiotic use in livestock and the development of antibiotic resistance.
Keywords: Framing; Public Opinion; Livestock; Antibiotic Resistance